Time to say goodbye? The role of SBIR funding, VC rounds, and initial alliance for director exit in new ventures - Chila, Vilma; van den Oever, Koen (Journal of Business Venturing, 2025)
Despite the significant interest in the composition and dynamics of new venture boards, our understanding of when directors exit the boards of new ventures is limited. Drawing on the organizational life cycles framework and resource dependence arguments, we posit that key life cycle events alter a venture's resource needs and dependencies on the board, occasioning director exit. Specifically, we argue that SBIR funding, Venture Capital rounds of funding, and first alliance act as markers of new venture evolution that render existing dependencies obsolete, increasing the likelihood of director exit. Interviews with board members in the semiconductor industry informed and substantiated our theoretical claims. The results show that SBIR funding and subsequent rounds of VC funding are linked to an increased likelihood of director exit, whereas a venture's first alliance is not. The paper sheds light on the interdependencies between the board's life cycle and the life cycle of the new venture.